USING CLICK AND CLUNK STRATEGY TO IMPROVE READING COMPREHENSION - Fadiel, Mohamad; Mukrim, Mukrim; Patmasari, Andi; Dewi, Anjar Kusuma (Tadulako University, 2025)
The objective of this research is to find out whether the click and clunk strategy can improve reading comprehension of the eighth-grade students of SMP Negeri 14 Palu. This research used a quantitative method and a quasi-experimental design. The population of this research was eighth-grade students of SMP Negeri 14 Palu with consisting of 128 students. The researchers used random sampling and adapted two groups: VIII Imam Bonjol and VIII Slamet Riyadi (experimental and control). The instrument of this research was a test, which was divided into two tests (pre-test and post-test). The result of this research showed that there were significant differences of students’ reading comprehension after being taught through KWL where the data analysis show that value of t-counted (1.908) is higher that the value of t-table (1.683) by applying a significance level of 0.05 with a degree of freedom (df) = 42. It means that the hypothesis is accepted. In other words, it means that the use of click and clunk strategy can improve students’ reading comprehension of the eighth grade students of SMP Negeri 14 Palu.